The concept, essence and types of tourist activity in the Republic of Kazakhstan - Aliyeva, L.R.; Kizdarbekova, A.S.; Klyueva, E.N. (KSU Publ., 2020)
This scientific article discusses the basic provisions on the concept, essence and types of tourist activity in the Republic of Kazakhstan. The authors study the main specifics of tourist activities in the Republic of Kazakhstan at the present stage. Attention is drawn to the fact that today the sphere of tourist activity is one of the most significant and priority areas of the modern economy of any civilized state, which is aimed at satisfying the requirements of people and improving the quality of their lives. In addition to studying the current legislation of the Republic of Kazakhstan, the authors of the article also, within the framework of a comparative analysis, turn to the legislation of the Russian Federation, first of all, to the provisions of Federal Law No. 132-FL «On the Basics of tourist activity in the Russian Federation» (dated November 24, 1996). The methodological basis of this scientific work was made up of dialectic, systemic, comparative legal, normative and other methods of cognition. This article discusses some classifications of types of tourism that currently exist. Tourist product is characterized as the basis of all tourist activities. The components of the tourism product, as well as its main consumer properties, are considered. It is concluded that by creating the most favored nation treatment for travel agencies, the legal and regulatory framework in the sphere of tourism, the state provides equal conditions for the implementation of tourist activities by legal entities and individuals, and promotes the development of international cooperation. The authors of this study pay due attention to the features of tour operator activities and travel agents in the tourist market.
Қазақстан Республикасындағы туристік қызмет ұғымы, мəні жəне түрлері
Понятие, сущность и виды туристской деятельности в Республике Казахстан
Keywords: tourist activity; tourism; tourist; types of tourism; tourist product; tour operator activity; travel agent activity; legislation on tourist activity; functions of tourist activity